The Gilfillan killings : narrative, marginality and the strangeness of the colonial past : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Loveridge, Greg (Massey University, 2003)
This thesis is about the process of telling stories. In particular, a group of stories centred on a disturbing moment in New Zealand history. The killing of the Gilfillan family was a brutal and unprecedented event, shocking the European population of New Zealand in 1847, and maintaining an ability to discomfort even 150 years later. The following pages are not an attempt to write the 'true' story of the Gilfillan killings, but rather to consider what made the killings shocking and disturbing in the first instance, and, how that power to shock and disturb can give a greater access to a historical moment. The focus is on how fragments of the past can maintain an aesthetic power in the present, and how an event becomes a cultural object, entangled in context and culture, and constantly renegotiated and re-narrated over time.The killing of the Gilfillans is normally called the "Gilfillan massacre", or the "Gilfillan murders". Both these phrases prejudge their deaths as criminal and 'savage' acts - whereas for the Maori involved they were at least partially political. Whatever the judgement of the morality of the killing of the children, I find the phrase "Gilfillan killings", more neutral, without eliding the violence of the event. One recent writer David Young (Young, David, Woven by Water: Histories from the Whanganui River, Wellington: Huia, 1998) has used the phrase the "Gilfillan muru" (killing). While I have avoided the use of the word "massacre", as it feels so redolent with colonial overtones, I feel no need to place the killings in a solely Maori cultural sphere - although in itself, by bringing a conception of the plurality of cultural responses to the killings, Young's act of renaming has strong points. A key assertion is that the story of the Gilfillan killings is marginal; outside the bounds of 'normal' experience. The marginal story, uncomfortable, disorientating, or difficult to understand and contexualise, is a way to puncture and break through explanatory meta-narratives which overwrite the particularity and contingency of history. To use a phrase borrowed from the school of literary criticism called Russian Formalism, it can 'make things strange', offering a new way of seeing and understanding the world. Boris Eichenbuam, "The Theory of Formal Method" in The Norton Anthology of Theory and Criticism, Vincent B. Leitch, gen. ed., New York, London: Norton Press: 2001, pp. 1062-87. To the Russian formalists the "roughened form" of great literature "defamiliarised" or "made things strange", breaking through "automatism" - normalised habits of perception. Analysing the marginal, strange-making story as a 'way in' to a historical past is a technique that has been used by a number of historians, particularly in the last few decades, as postmodernism and the influence of other disciplines, such as anthropology, began to move historical practice away from broader explanatory meta-narratives towards more historically specific and culturally situated explanations. A famous example is the description of the execution at the beginning of Michel Foucault's Discipline and Punish.4 4 Michel Foucault, Discipline and Punish: the Birth of the Prison, translated from the French by Alan Sheridan, New York: Pantheon Books, cl977. pp. 1-3. The image of the pincers tearing flesh from the condemned body of Damiens the Regicide is an access point into a different "mentalite", a different set of cultural conceptions of justice, whose obvious distance from more modern understandings leads to the renewed investigation of the underlying precepts of each.
Keywords: Rhetoric narration; Cultural relativism; Gillfillan family; New Zealand Wars, 1843-1847; Putiki; Wanganui District; History